Persistent free-floating pelvic trophoblastic cysts following an interstitial ectopic pregnancy. Issue 8 (21st August 2019) - Crawford, Kaitlin D; Chen, Melissa J; Hou, Melody Y; Creinin, Mitchell D
Abstract : Persistent trophoblast after ectopic pregnancy has been demonstrated at the surgical site or as peritoneal implants. A 37-year-old woman (G5P2) experienced persistently low levels of beta-human chorionic gonadotropin (hCG) after surgical treatment for an interstitial pregnancy. Evaluation for persistent trophoblast, gestational trophoblastic neoplasm and heterophilic antibodies was negative. After 15 months without resolution, she elected for hysterectomy. We found four smooth, freely floating avascular cysts intraoperatively; pathological evaluation identified the cysts as trophoblastic tissue. Serum beta-hCG resolved postoperatively and remained negative at 1 year. Our case demonstrates the novel finding of trophoblastic tissue existing as free-floating cysts in the peritoneal cavity. With appropriate suspicion, these cysts can be identified on radiologic investigation and removed laparoscopically.